Report of the 4th workshop on the African opportunity crops working group under the SUSTLIVES project - Grazioli, Francesca; Otieno, Gloria; Mendonce, Sharon; Acasto, Filippo; El Bilali, Hamid (2025)
This report highlights the outcomes of a high-level workshop convened under the EU-funded SUSTLIVES project, which promotes the strategic use of neglected and underutilized species (NUS)—now repositioned as “opportunity crops”—to enhance food and nutrition security, support resilient livelihoods, and contribute to climate adaptation in Burkina Faso and Niger. The workshop was held on September 2 at the Axil Hotel in Dakar, Senegal.